How Much GOTV Mail is Too Much? Results from a Large-Scale Field Experiment. Issue 2 (13th September 2017) - Green, Donald P.; Zelizer, Adam
Abstract: This study evaluates the turnout effects of direct mail sent in advance of the 2014 New Hampshire Senate election. Registered Republican women were sent up to 10 mailings from a conservative advocacy group that encouraged participation in the upcoming election. We find that mail raises turnout, but no gains are achieved beyond five mailers. This finding is shown to be consistent with other experiments that have sent large quantities of mail. We interpret these results in light of marketing research on repetitive messaging.